Academic self-handicapping behaviour and student engagement among the students of the International Islamic University Malaysia - Mwita, Hafsa Mzee (Institute of Education, International Islamic University Malaysia, 2014)
The main purpose of the present study is to develop and validate the model of predictors of academic self-handicapping (POASH) on the data derived from undergraduate students in an ongoing co-curriculum compulsory course. The study adapted and extended the original theory of reciprocal interaction of emotion, cognition and behavior by adding self-handicapping behavior component. Consequently, this study assessed the direct and indirect effects of emotion, cognition and behavior via student engagement on self-handicapping behaviour (SHB). The data was collected from two self-reported questionnaires administered to 790 undergraduates of the International Islamic University in Malaysia. A confirmatory three-step approach theory testing and development using Maximum Likelihood method was applied by using AMOS version 16. Results proved that, the three factor measurement model is empirically fit and reliable. This enhanced the formulation of the partial disaggregation model of “Predictors of Academic Self-Handicapping” (POASH) which consists of one latent variable and three manifest variables. The results of structured equation modeling supported the adequacy of POASH model and the causal structure of POASH model proved to be applicable to both genders and nationality statuses. Among other findings the research produced empirical evidence that scores of student engagement were negatively predicting (20%) of academic self-handicapping behavior; with male student predicting SHB with higher scores (25%) than female students (21%). And with a significant prediction of national students scores (25%) of SHB while international students revealed insignificant prediction score (12%) of SHB, Moreover, the results of gender invariance revealed that behavioral engagement is relatively more influential (70%) than both emotional and cognitive engagement in influencing SHB, while emotional engagement influences SHB more (55%) than the cognitive engagement (31%) does. Therefore, the findings of this study suggest that emotional engagement, behavioral engagement and cognitive engagement are significant negative predictors of academic self-handicapping with significantly higher prediction of behavioral engagement, followed by emotional engagement and lastly by cognitive engagement on academic self-handicapping. Thus, improving the depth of students' academic engagement skills in order to counteract academic self-handicapping behavior and to improve student achievement becomes inevitable. More studies on self-handicapping and student engagement are therefore recommended.